Infection and acute respiratory distress syndrome during pregnancy: A case series of preventable maternal deaths from southern India - Akhila Vasudeva; Rajeshwari G. Bhat; Amar Ramachandran; Pratap Kumar (Elsevier, 2013)
Summary: Introduction: Acute respiratory distress syndrome (ARDS) is common among women admitted to obstetric intensive care units, and it contributes significantly, both directly and indirectly, to maternal deaths. Case series: We present a case series of ARDS in pregnant women caused by non-obstetric causes. The women were treated at a tertiary hospital in southern India. The striking features were delayed referral from the primary care unit and the lack of a primary diagnosis or treatment. Undiagnosed rheumatic heart disease, anemia, and malaria and H1N1 epidemics contributed to these cases of ARDS and maternal death. Conclusion: It is necessary to increase the awareness of evidence-based uniform protocols to tackle common medical complaints during pregnancy. Keywords: Acute respiratory distress syndrome (ARDS), Pregnancy, Maternal mortality